2011
DOI: 10.1182/blood-2010-10-314120
|View full text |Cite
|
Sign up to set email alerts
|

mpeg1 promoter transgenes direct macrophage-lineage expression in zebrafish

Abstract: Macrophages and neutrophils play important roles during the innate immune response, phagocytosing invading microbes and delivering antimicrobial compounds to the site of injury. Functional analyses of the cellular innate immune response in zebrafish infection/ inflammation models have been aided by transgenic lines with fluorophore-marked neutrophils. However, it has not been possible to study macrophage behaviors and neutrophil/macrophage interactions in vivo directly because there has been no macrophage-only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,049
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 935 publications
(1,077 citation statements)
references
References 41 publications
26
1,049
0
2
Order By: Relevance
“…3B, n ϭ 13). The injured embryos were immediately viewed under a confocal microscope at 3-min intervals for 48 h. Results showed that, similar what was noted in the previous reports (14,15), both types of myeloid cells responded immediately, but they migrated into the wound at different speeds (Fig. 3, A-D, n Ն 9; supplemental Movie 1, n ϭ 3).…”
Section: Neutrophils Are the Primary Scavengers During Inflammation Ssupporting
confidence: 84%
See 1 more Smart Citation
“…3B, n ϭ 13). The injured embryos were immediately viewed under a confocal microscope at 3-min intervals for 48 h. Results showed that, similar what was noted in the previous reports (14,15), both types of myeloid cells responded immediately, but they migrated into the wound at different speeds (Fig. 3, A-D, n Ն 9; supplemental Movie 1, n ϭ 3).…”
Section: Neutrophils Are the Primary Scavengers During Inflammation Ssupporting
confidence: 84%
“…By utilizing the Tg(coro1a:eGFP;lyz:Dsred) double transgenic lines, the in vivo behaviors and functions of macrophages and neutrophils in the larva tail fin regeneration (14,15,38,39) were directly assayed in a living embryo. We showed that upon injury, the local resident macrophages and neutrophils (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The casper mutant 56 and Tg(gata1::DsRed) 57 lines were previously described. The transgenics lines Tg(lyz::DsRed) 25 , Tg(mpx::eGFP) 24 , Tg(mpeg1::GAL4/uas::NTRmCherry) (mpeg1::mCherry was used throughout this manuscript for clarity) 26 and Tg(cd41::eGFP) 31 were kindly provided by Drs P. Crosier, S. Renshaw, G. Lieschke and R.I. Handin, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2b). To examine whether macrophages were affected, a tg(mpeg1:mCherry) line was used that has red fluorescent macrophages 26 . The number of macrophages was also reduced in TR-deficient larvae (Fig.…”
mentioning
confidence: 99%
“…However, cells of the mature adaptive immune system emerge later, at around 1 week of larval life [49,50], giving us the advantage of distinguishing between the contribution of the innate immune cells and the adaptive immune system in various processes involving the immune system in larval zebrafish. Moreover, zebrafish transgenic lines that have fluorescently labeled leukocyte subtypes in different colors are available [51][52][53], allowing easy in vivo observations under a fluorescent microscope. Zebrafish melanoma models were used by Feng [54] to delineate possible early interactions between oncogenetransformed melanoblasts and goblet cells and the immune system in the skin of zebrafish larvae.…”
Section: Melanoma and Immune Cellsmentioning
confidence: 99%